Competency model of training in psychotherapy integration - Kostínková, Jana; Řiháček, Tomáš; Roubal, Jan; Horváth, Adam (European Journal for Qualitative Research in Psychotherapy, 2023)
Competency models can be a cornerstone of the development of effective education in psychotherapy. This study aimed to develop a competency model for the Training in Psychotherapy Integration program in the Czech Republic. Method: The model was developed using the principles of cooperative inquiry and action research. Six trainers and three researchers participated in the study. Data were drawn from focus groups and individual interviews held with trainers and from archival materials of the training program. The research process involved several cycles of data collection, qualitative analysis, implementation, and feedback. Results: The Training in Psychotherapy Integration competency model was organized into three domains focusing on the therapeutic relationship, the client, and the therapist. Each domain was further divided into three layers, namely: personal, procedural, and contextual. Conclusion: The Training in Psychotherapy Integration competency model proved useful and contributed to the training program in several respects, providing identity, structure, a path to consensus, and a trainee evaluation tool.